Beneficial effects of adenosine triphosphate-sensitive K+ channel opener on liver ischemia/reperfusion injury - Nogueira, Mateus Antunes; Coelho, Ana Maria Mendonça; Sampietre, Sandra Nassa; Patzina, Rosely Antunes; Pinheiro da Silva, Fabiano; D'Albuquerque, Luiz Augusto Carneiro; Machado, Marcel Cerqueira Cesar (World journal of gastroenterology : WJG, 2014)
To investigate the effect of diazoxide administration on liver ischemia/reperfusion injury. Wistar male rats underwent partial liver ischemia performed by clamping the pedicle from the medium and left anterior lateral segments for 1 h under mechanical ventilation. They were divided into 3 groups: Control Group, rats submitted to liver manipulation, Saline Group, rats received saline, and Diazoxide Group, rats received intravenous injection diazoxide (3.5 mg/kg) 15 min before liver reperfusion. 4 h and 24 h after reperfusion, blood was collected for determination of aspartate transaminase (AST), alanine transaminase (ALT), tumor necrosis factor (TNF-α), interleukin-6 (IL-6), interleukin-10 (IL-10), nitrite/nitrate, creatinine and tumor growth factor-β1 (TGF-β1). Liver tissues were assembled for mitochondrial oxidation and phosphorylation, malondialdehyde (MDA) content, and histologic analysis. Pulmonary vascular permeability and myeloperoxidase (MPO) were also determined. Four hours after reperfusion the diazoxide group presented with significant reduction of AST (2009 ± 257 U/L vs 3523 ± 424 U/L, P = 0.005); ALT (1794 ± 295 U/L vs 3316 ± 413 U/L, P = 0.005); TNF-α (17 ± 9 pg/mL vs 152 ± 43 pg/mL, P = 0.013; IL-6 (62 ± 18 pg/mL vs 281 ± 92 pg/mL); IL-10 (40 ± 9 pg/mL vs 78 ± 10 pg/mL P = 0.03), and nitrite/nitrate (3.8 ± 0.9 μmol/L vs 10.2 ± 2.4 μmol/L, P = 0.025) when compared to the saline group. A significant reduction in liver mitochondrial dysfunction was observed in the diazoxide group compared to the saline group (P < 0.05). No differences in liver MDA content, serum creatinine, pulmonary vascular permeability and MPO activity were observed between groups. Twenty four hours after reperfusion the diazoxide group showed a reduction of AST (495 ± 78 U/L vs 978 ± 192 U/L, P = 0.032); ALT (335 ± 59 U/L vs 742 ± 182 U/L, P = 0.048), and TGF-β1 (11 ± 1 ng/mL vs 17 ± 0.5 ng/mL, P = 0.004) serum levels when compared to the saline group. The control group did not present alterations when compared to the diazoxide and saline groups. Diazoxide maintains liver mitochondrial function, increases liver tolerance to ischemia/reperfusion injury, and reduces the systemic inflammatory response. These effects require further evaluation for using in a clinical setting.